Optimization of heterologous DNA-prime, protein boost regimens and site of vaccination to enhance therapeutic immunity against human papillomavirus-associated disease. Issue 1 (December 2016) - Peng, Shiwen; Qiu, Jin; Yang, Andrew; Yang, Benjamin; Jeang, Jessica; Wang, Joshua; Chang, Yung-Nien; Brayton, Cory; Roden, Richard; Hung, Chien-Fu; Wu, T.-C.
Abstract Background Human papillomavirus (HPV) has been identified as the primary etiologic factor of cervical cancer as well as subsets of anogenital and oropharyngeal cancers. The two HPV viral oncoproteins, E6 and E7, are uniquely and consistently expressed in all HPV infected cells and are therefore promising targets for therapeutic vaccination. Both recombinant naked DNA and protein-based HPV vaccines have been demonstrated to elicit HPV-specific CD8+ T cell responses that provide therapeutic effects against HPV-associated tumor models. Here we examine the immunogenicity in a preclinical model of priming with HPV DNA vaccine followed by boosting with filterable aggregates of HPV 16 L2E6E7 fusion protein (TA-CIN). Results We observed that priming twice with an HPV DNA vaccine followed by a single TA-CIN booster immunization generated the strongest antigen-specific CD8+ T cell response compared to other prime-boost combinations tested in C57BL/6 mice, whether naïve or bearing the HPV16 E6/E7 transformed syngeneic tumor model, TC-1. We showed that the magnitude of antigen-specific CD8+ T cell response generated by the DNA vaccine prime, TA-CIN protein vaccine boost combinatorial strategy is dependent on the dose of TA-CIN protein vaccine. In addition, we found that a single booster immunization comprising intradermal or intramuscular administration of TA-CIN after priming twice with an HPV DNA vaccine generated a comparable boost to E7-specific CD8+ T cell responses. We also demonstrated that the immune responses elicited by the DNA vaccine prime, TA-CIN protein vaccine boost strategy translate into potent prophylactic and therapeutic antitumor effects. Finally, as seen for repeat TA-CIN protein vaccination, we showed that the heterologous DNA prime and protein boost vaccination strategy is well tolerated by mice. Conclusions Our results provide rationale for future clinical testing of HPV DNA vaccine prime, TA-CIN protein vaccine boost immunization regimen for the control of HPV-associated diseases.